2021
DOI: 10.1177/23328584211010180
|View full text |Cite
|
Sign up to set email alerts
|

Cross-National Variation in School Reopening Measures During the COVID-19 Pandemic

Abstract: To contain the initial spread of the SARS-CoV2 virus and the COVID-19 disease, many countries opted to close schools. However, the importance of schooling to mitigate inequalities motivated many economies to reopen schools after having formulated various COVID-19 mitigation and containment strategies. Using an exploratory sequential mixed method design, we explore the measures undertaken by countries when reopening schools and how these measures varied cross-nationally. We find that countries formulated a wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Quarantining can also negatively affect resilience and relationships, and research has shown that students who experienced quarantine following a natural disaster were more likely to show symptoms consistent with PTSD (Sprang & Silman, 2013). Although the majority of U.S. PK–12 students have now returned to in-person instruction, there was considerable variability at the start of the 2020–2021 academic year, with some remaining fully remote (Hoffman et al, 2021), with corresponding mental health consequences (Duckworth et al, 2021). Regardless, all students likely experienced some level of mandated quarantine (Stevens, 2020) and may have lingering distress as a result.…”
Section: Likely Mental Health Impacts Of Covid-19 On Pk–12 Studentsmentioning
confidence: 99%
“…Quarantining can also negatively affect resilience and relationships, and research has shown that students who experienced quarantine following a natural disaster were more likely to show symptoms consistent with PTSD (Sprang & Silman, 2013). Although the majority of U.S. PK–12 students have now returned to in-person instruction, there was considerable variability at the start of the 2020–2021 academic year, with some remaining fully remote (Hoffman et al, 2021), with corresponding mental health consequences (Duckworth et al, 2021). Regardless, all students likely experienced some level of mandated quarantine (Stevens, 2020) and may have lingering distress as a result.…”
Section: Likely Mental Health Impacts Of Covid-19 On Pk–12 Studentsmentioning
confidence: 99%
“…Faced with the need to minimize such harms while minimizing the role of schools in transmission, many countries reopened schools while implementing various preventive measures. 16 , 17 , 18 , 19 , 20 While evidence suggests that schools in the United Kingdom are implementing a large number of preventive measures 16 , 17 which are likely to reduce COVID‐19 transmission, 21 there is little evidence on the fidelity of implementation of different measures, the challenges they raise for schools, or the extent to which students adhere to them.…”
mentioning
confidence: 99%
“…Eventually, a total of five papers that had roadmaps and focused on reopening the schools were included in this study[ 28 29 30 31 32 ][ Table 1 ].…”
Section: Resultsmentioning
confidence: 99%